Clima laboral y satisfacción personal en docentes de la Institución Educativa "Rosa de América" Iquitos 2015 - Contreras Estrella, Gina Paoli (2018)
The objective of this research was: To determine the extent to which it correlates the Work Climate and Personal Satisfaction in Teachers of the Educational Institution "Rosa de América" - Iquitos 2015. The problems raised in the study are: To what extent does the Work Climate and Personal Satisfaction in Teachers of the Educational Institution "Rosa de America" in Iquitos correlate in 2015?. The study belonged to correlational research because it allowed to know the degree of correlation between the variables: Work Climate and Personal Satisfaction. The research design was that of the non-experimental research and the specific design was the correlational transectional one. the population consisted of 47 teachers and and the sample was represented by 100%of the population. The selection of the sample was intentionally non-probabilistic. The results show that the work environment correlates with personal satisfaction with a magnitude greater than 40%. It was concluded that the work environment correlates with a magnitude greater than 40% with personal satisfaction in teachers of the “Rosa de América” Educational Institution in Iquitos in 2015. We recommend to the directors of the “Rosa de América” Educational Institution in Iquitos, to raise their work environment so that the personnel working in said organization are 100% satisfied.